2015
DOI: 10.1097/bot.0000000000000359
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Fracture Stability on Early Patient Mortality and Reoperation After Pertrochanteric and Intertrochanteric Hip Fractures

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
3
28
2
3
Order By: Relevance
“…We found that the AO/OTA type 31-A1 and 31-A2 fractures, which are sometimes referred to as stable, were most common (78%). This finding is similar to Chehade et al [ 20 ] who in 2015 published a prospective consecutive cohort of 743 patients were the majority (60%) were classified as stable trochanteric and only 40% as unstable trochanteric or subtrochanteric fractures. We found that with increasing fracture complexity, the proportion of intramedullary nails was increasing, and also the use of long versus short nails.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the AO/OTA type 31-A1 and 31-A2 fractures, which are sometimes referred to as stable, were most common (78%). This finding is similar to Chehade et al [ 20 ] who in 2015 published a prospective consecutive cohort of 743 patients were the majority (60%) were classified as stable trochanteric and only 40% as unstable trochanteric or subtrochanteric fractures. We found that with increasing fracture complexity, the proportion of intramedullary nails was increasing, and also the use of long versus short nails.…”
Section: Discussionsupporting
confidence: 89%
“… 18 The impact of mean interval between the incidence of fracture and surgery was also carried out the results revealed that delay in surgery probably increases the likelihood of complications. 17 The reason for this delay could be related to the patient’s late referral to our hospital and also for treatment of their underlying diseases to ready for anesthesia and surgical procedure. However the delay due to surgery would not seem to have adverse effect on the mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Both current and prior investigators did not find value in conducting EPI studies for patients who underwent IFF CRIF, even when the fractures were defined pre-operatively as unstable or the fixations were sub-optimal [ 15 , 22 , 26 ]. Furthermore, the current study found that too early radiographs did not provide new information and were of low quality because it was difficult for patients to cooperate with positioning on the radiography table due to post-operative pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%